2019
DOI: 10.1111/jcmm.14424
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive epigenetic analyses reveal master regulators driving lung metastasis of breast cancer

Abstract: The lung metastasis of breast cancer involves complicated regulatory changes driven by chromatin remodelling. However, the epigenetic reprogramming and regulatory mechanisms in lung metastasis of breast cancer remain unclear. Here, we generated and analysed genome‐wide profiles of multiple histone modifications (H3K4me3, H3K27ac, H3K27me3, H3K4me1 and H3K9me3), as well as transcriptome data in lung‐metastatic and non‐lung‐metastatic breast cancer cells. Our results showed that the expression changes were corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Another group of TFs identified in our study provide novel avenues for exploration. For instance, TFAP2C expression was significantly associated with lung relapses, consistent with a recent study [27]. TFAP2C is a pioneer factor that plays important roles in pluripotency and lineage differentiation [87,88].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Another group of TFs identified in our study provide novel avenues for exploration. For instance, TFAP2C expression was significantly associated with lung relapses, consistent with a recent study [27]. TFAP2C is a pioneer factor that plays important roles in pluripotency and lineage differentiation [87,88].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the technique used in this study, omni-ATAC-seq, has been shown to have the same robustness for TF binding prediction as the previous gold standard DNAase-seq [85]. Our pipeline uncovered robust candidate epigenetic markers of relapse that were not identified by previous reports using ChIP-Seq only [27]. These TFs may help establish or maintain chromatin states which are permissive for the expression of prometastatic gene expression programs.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Young and colleagues found that H3 lysine 27 acetylation (H3K27ac) is the label for super ehnancers, 34,35 which makes chromatin structures looser, providing ideal sites for active transcription machine. In addition, master transcription factors tend to co-bind at the SEs ( Figure 1A).…”
Section: Histone Modification and Chromatin Remodellingmentioning
confidence: 99%
“…2,3 However, for patients with advanced BC, the efficacies of surgery and chemotherapy are low due to distant metastasis of cancer. 4 Distant metastasis is an important factor contributing to BC development, [5][6][7] and many BC patients have metastatic BC at the time of diagnosis, and their 5-year survival rates are only *27%. 8 Similar to other cancers, the occurrence, development, and metastasis of BC are closely related to the abnormal expressions of multiple genes such as oncogenes, tumor-suppressor and metastasisrelated genes.…”
Section: Introductionmentioning
confidence: 99%